Estimation of losses in grain yield due to bacterial blight and neck blast of rice in Haryana - and D.S. DODAN, RAM SINGH*, S. SUNDER (Indian Phytopathology, 2013)
Field experiments were conducted at CCSHAU Rice Research Station, Kaul during kharif 2008 to 2011 to study the effect of time of inoculation of bacterial blight pathogen (Xanthomonas oryzae pv. oryzae) and varied levels of incidence and severity of neck blast on grain yield and yield attributes of non-scented and scented rice varieties. Inoculation of bacterial blight pathogen 30 days after transplanting (DAT) resulted in a maximum mean yield loss of 29.88% followed by inoculation at 45 DAT while the losses were minimum when rice varieties were inoculated at 75 DAT. Among the varieties, the overall mean yield loss was maximum in Pusa Basmati-1 (35.76%) followed by CSR 30 and Haryana Shankar Dhan-1 while it was minimum in HKR 47. The maximum yield loss was recorded in Pusa Basmati-1 (45.14%) followed by Haryana Shankar Dhan-1 (31.29%) while it was minimum in HKR 47 (22.62%) when inoculated at 30 DAT. The corresponding losses in grain yield of these cultivars were 22.44, 5.38 and 1.53% when inoculated at 75 DAT. There was a significant increase in per cent chaffy grains (5.47 to 17.53%) with increasing levels of neck blast incidence from 30 to 100% while 1000 grain weight and grain yield of 100 panicles was reduced by 7.52 to 23.88% and 1.77 to 37.52%, respectively as the disease incidence increased from 0 to 100%. With regards to neck blast severity, the chaffy grains increased from 5.00 to 28.48% while 1000 grain weight and grain yield of 100 panicles decreased by 0.73 to 33.81% and 1.49 to 59.80% as the neck blast severity increased from grade 1 (panicles with small lesions without engirdling of the neck region) to grade 3 (completely engirdled panicles), respectively.